1987
DOI: 10.1128/jvi.61.5.1421-1426.1987
|View full text |Cite
|
Sign up to set email alerts
|

Simian immunodeficiency virus induces expression of class II major histocompatibility complex structures on infected target cells in vitro

Abstract: The human immunodeficiency virus (HIV) and the closely related simian immunodeficiency virus (SIV) induce profound immune dysfunction in primate species. The present studies show that cell populations infected in vitro with SIV exhibit increases in major histocompatibility complex (MHC) class II antigen expression. Cell lines chronically infected with both the monkey and human viruses express substantially more MHC class H but not more lineage-restricted or activation antigens on their membranes than do uninfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The upregulation of MHC class II noted in these ex vivo studies has also been reported with in vivo infection by FIV (Ohno et al, 1992;Rideout et al, 1992;Hunt and McConnell, 1995). Similar observations have also been noted with infections by HIV-1 (Cantin et al, 1997a, b) and SIV (Kannagi et al, 1987). At first glance, this would seem to be a counterproductive move for the virus in that it would, via class II-bound virus peptide, signal the immune system that the cell was infected and target it for clearing.…”
Section: Discussionsupporting
confidence: 84%
“…The upregulation of MHC class II noted in these ex vivo studies has also been reported with in vivo infection by FIV (Ohno et al, 1992;Rideout et al, 1992;Hunt and McConnell, 1995). Similar observations have also been noted with infections by HIV-1 (Cantin et al, 1997a, b) and SIV (Kannagi et al, 1987). At first glance, this would seem to be a counterproductive move for the virus in that it would, via class II-bound virus peptide, signal the immune system that the cell was infected and target it for clearing.…”
Section: Discussionsupporting
confidence: 84%
“…Infection and cellular activation. Lentivirus infection leads to increased expression of MHC class II antigens, an activation marker, on macrophages in infected sheep (32) and also in macaque cells (14,31) following infection. This prompted our investigation of the effect of virus inoculation on expression of activation antigens on PBMC.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies [26,271, y-interferon-independent CMV-induced class I1 expression was recorded in rat heart endothelial cells in culture. Also, direct virus-induced class I1 expression has been demonstrated in other types of cells [12,17,181, indicating that viral agents, during binding, penetration, or replication, can cause some y-interferon-independent events that lead to class I1 expression in the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Class I1 expression, CMV. rat rect viral induction of class I1 molecules has been described for different cell types [12,17,18]. WF have previously demonstrated CMV-induced class I1 expression in rat heart endothelial cells in thdabsence of interferony [26,27], which suggests that a direct mechanism of upregulation of class I1 expression by the CMV might exist, at least in vitro.…”
Section: Introductionmentioning
confidence: 99%